Emulation platform for inter-domain protocols validation of integrated space-terrestrial network - Zengyin YANG; Hewu LI; Qian WU; Jianping WU; Jun LIU (Tongxin xuebao)
The inter-domain routing protocol is a key factor in the rapid integration of various satellite systems and heterogeneous networks in integrated space-terrestrial network (ISTN).However,the wide difference between network topologies of space and terrestrial networks may present significant challenges to the deployment of existing inter-domain protocols.To test the performance of these protocols,an emulation platform for ISTN was designed to efficiently emulate the dynamic and large-scale space network and the existing terrestrial networks using virtual network technology.Extensive experiments demonstrate that,with the expansion of the scale of space network and the scale of terrestrial Internet’s routing table,the integration efficiency between space and terrestrial networks becomes very low.